Improving the Ability to Write Descriptive Texts Through the Word Game Method in Class VII Students of SMPN 2 Gunung Bintang Awai - Masita Masita; Kastam Syamsi (FKIP - Universitas Riau, 2026)
The background of the research is that the Indonesian language learning process at SMP Negeri 2 Gung Bintang Awal still uses conventional learning methods such as lecture methods and low Indonesian language learning outcomes. The study aims to improve the ability to write descriptive texts through word play methods in grade VII students of SMP Negeri 2 Gunung Bintang Awai. The type of research is Classroom Action Research (CAR) which is carried out in two cycles with each cycle consisting of planning, implementation, observation, and reflection stages. The subjects of this study were 28 students of Grade VII of SMP Negeri 2 Gunung Bintang Awai. The research was conducted at SMP Negeri 2 Gunung Bintang Awai. Research data were collected through observation, reading tests, and documentation, then analyzed qualitatively and quantitatively. The results of the study are that the application of the word play method can improve the ability to write descriptive texts in grade VII students of SMP Negeri 2 Gunung Bintang Awai both in terms of process and product. Improving the quality of the process has a positive impact on improving the quality of the results. This can be seen from the results of the descriptive text writing test from the pre-action stage to cycle II, which experienced an increase, namely at the pre-action stage it was 62.14, at cycle I stage it was 72.32 and at cycle II stage it was with an average value of 78.56. It can be concluded that word play is a writing strategy that can improve the ability to write descriptive text.